Karakteristik Mekanik Komposit Polymeric Foam Dengan Matriks Polyester Resin Serat Tandan Kosong Sawit (TKS), Serat Pinang, Dan Kombinasi Serat TKS-Pinang - Irawan, Agung Dwi; Badri, Muftil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
In this era, research application of composite such as furniture, aerospace, automotive components made from synthetic fibers. Natural fibers can substitute of synthetic fibers. The one of natural fiber oil palm empty fruits bunch (OPEFB) is composite was waste residue of the processing palm oil utilization which use as compost and fuel of combustion proces in boiler palm oil mill. Generally, the part of areca usually use is nut, while fibers are throw 5% NaOH for 4 hours and boiling distilled water for 1 hour as a composite of a polymeric foam to the mechanical properties of the composite. OPEFB and areca fibers use as the reinforcement and polyester resin use as matrix. In this research, method of manufacture used Vacuum Assisted Resin Infusion (VARI). The results showed the highest value of yield strength 4.76 MPa, tensile strength 16.08 MPa, fracture strength 16.08 MPa in the areca fiber composite treatment NaOH 5%, for modulus elasticity 22.49 GPa in the areca fiber treatment of boiling distilled water, strain total 7.81% in the OPEFB fiber composite treatment immersion of 5% NaOH. Impact price 1.38 J/mm2 in the OPEFB fiber composite treatment immersion of 5% NaOH. Keywords : areca fiber, boiling distilled water, NaOH 5%, OPEFB, polyester resin, VARI